Factors influencing patient experience in hospital wards: a systematic review - Tingyu Guan; Xiao Chen; Junfei Li; Yuxia Zhang (BMC, 2024)
Abstract Background Patient experience plays an essential role in improving clinical effectiveness and patient safety. It's important to identify factors influencing patient experience and to improve quality of healthcare. Objective To identify factors that influence patient experience in hospital wards. Methods We conducted a systematic review including six databases; they were PubMed, CINAHL, Embase, PsycInfo, ProQuest, and Cochrane. Studies were included if they met the inclusion criteria. The JBI checklist was used to perform quality appraisal. We used 5 domains of the ecological model to organize and synthesize our findings to comprehensively understand the multi-level factors influencing the issue. Result A total of 138 studies were included, and 164 factors were identified. These factors were integrated into 6 domains. All domains but one (survey-related factors) could be mapped onto the attributes of the ecological framework: intrapersonal, interpersonal, institutional, community, and public policy level factors. All factors had mixed effect on patient experience. The intrapersonal level refers to individual characteristics of patients. The interpersonal level refers to interactions between patients and healthcare providers, such as the caring time spent by a nurse. The institutional level refers to organizational characteristics, rules and regulations for operations, such as hospital size and accreditation. The community level refers to relationships among organizations, institutions, and informational networks within defined boundaries, such as a hospital located in a larger population area. Public policy level refers to local, state, national, and global laws and policies, including health insurance policies. The sixth domain, survey-related factors, was added to the framework and included factors such as survey response rate and survey response time. Conclusion The factors influencing patient experience are comprehensive, ranging from intrapersonal to public policy. Providers should adopt a holistic and integrated perspective to assess patient experience and develop context-specific interventions to improve the quality of care. PROSPERO registration number CRD42023401066